P16INK4a deletion alleviates contrast-induced acute kidney injury by ameliorating renal cell apoptosis and suppressing inflammation and oxidative stress - Xiaodong Zhang; Guangyi Huang; Zhixuan Zhang; Fen Wang; Qian Liu; Yingqiang Du; Xiaoyan Wang; Xin Gu (Experimental Gerontology, 2024)
Contrast-induced acute kidney injury (CI-AKI) is the third leading cause of hospital-acquired acute kidney injury. Cellular senescence is associated with CI-AKI. P16INK4a (p16) is a cell cycle regulator and link to aging and senescence. We found that the expression of p16 was elevated in CI-AKI renal tissues, however its role in CI-AKI remains insufficiently understood. In this study, we used p16 knockout (p16KO) mice and wild-type (WT) littermates to establish CI-AKI mice model to elucidate the impact of p16 on CI-AKI. The results showed that serum creatinine (SCr), blood urea nitrogen (BUN), and serum neutrophil gelatinase-associated lipocalin (NGAL) levels were markedly reduced in p16KO CI-AKI mice. Both immunohistochemistry and western blot analyses confirmed that p16 knockout alleviated renal cell apoptosis. Furthermore, interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α) were attenuated by downregulating NLRP3 and NF-κB inflammasomes. Additionally, ROS levels were diminished via activating Nrf2/Keap-1 pathway in p16KO CI-AKI mice. Collectively, our findings suggest that p16 deletion exerts protective effects against apoptosis, inflammation, and oxidative stress in CI-AKI mice model, p16 deletion might be a potential therapeutic strategy for ameliorating CI-AKI.